Pelatihan dan pembimbingan flipbook sebagai media pembelajaran matematika di Yayasan Nurul Hasaniah - Karo Karo, Ichwanul Muslim; Rangkuti, Y. M; Gea, Kurnia Mildawati; Landong, Ahmad (Universitas Pendidikan Indonesia (UPI), 2023)
The learning process has been transformed into the digital era 4.0. Digital learning materials are needed to improve students' problem-solving skills and learning independence. Flipbooks are three-dimensional digital books that can contain text, images, videos, music or songs, and animations. Flipbooks can be used to teach mathematics, which is generally considered to be a difficult subject. Therefore, teachers are required to be able to prepare digital learning materials for mathematics. Yayasan Pendidikan Nurul Hasaniah focuses on organizing education from elementary school to high school, so the teacher must also be able to prepare digital learning materials. One of the efforts to improve the ability of teachers with training activities and flipbook guidance as a mathematics learning media. The results of the activity show that the teachers were able to use professional pdf flipbook software and are able to create e-modules.